Hard-milling using carbide cutters: Experimental investigation and optimization - Iqbal, Asif; He, Ning; Li, Liang (Nova Science Publishers, Inc., 2012)
Shortly after its renaissance the high-speed milling technology was applied to the machining of steels in their hardened state for manufacturing of molds and dies. Despite being harnessed by numerous advantages, the high-speed milling of hardened steels (also known as hard-milling) comes also with a major demerit, the demerit of dire shortening of tool life. The main aim of the research being done is the enhancement of tool life. Besides tool life, the requirements of fine surface finish and high material removal rate also gain considerable importance for the processes of finish milling and rough milling, respectively. For the simultaneous achievement of the aforementioned targets, series of hard-milling experiments, following statistical designs, were performed using tungsten carbide mill cutters. The effects of following parameters: workpiece material's microstructure and hardness, tool coating, helix angle, rake angle, milling-orientation, minimum quantity of lubrication (MQL), cutting speed, feed rate, radial depth of cut, and workpiece's inclination angle were investigated on following performance measures: tool life, roughness of workpiece's side surface and end surface, and cutting forces. Hard-milling experiments were subdivided into flat end milling and ball-nose end milling. The experimental results were analyzed using ANOVA and significances of effects of all the tested parameters, on performance measures, were determined. Scanning electron microscopy (SEM) and energy dispersive spectrometry (EDS) analyses were performed upon the surfaces of used tools in order to identify the major tool damage modes and their dependences upon the levels of milling parameters selected. From the results of post-experimental analyses, it was noticed that the effects of workpiece microstructure and hardness, tool coating, and milling-orientation on tool life are extremely significant, while the effects of cutting speed, MQL, feed rate, and helix angle are also considerably significant. The effects of rake angle and radial depth of cut are marginally significant. On the other hand, the surface roughness is highly sensitive to milling-orientation (side surface), workpiece's inclination angle, cutting speed, and radial depth of cut (end surface). SEM and EDS analyses showed that the major tool damage modes were chipping, adhesion, diffusion, and oxidation. High values of hardness and feed rate accelerate the chipping process and on the other hand, the up-milling and high values of cutting speed lead to thicker adhesion of workpiece particles upon tool's surface. © 2012 Nova Science Publishers, Inc. All rights reserved.